3-d kinematics of classical technique of elite cross-country skiers engaged in world championships races (Ramsau 1999 - Fiemme 2003) - Canclini, A.; Pozzo, R.; Moriconi, B.; Baroni, G. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Introduction: In the recent years the skating technique has received more attention from skiers, coaches, and researchers, to improve the racers performance, than the "old" classical technique. However the changes in the equipments, sometimes directly transferred from the skating technique, in the track and in the physiological aspects of the training determined great changes (CCS) also in classical technique. In both techniques the changes were in the average velocity (Vave), cycle time (CT) and cycle length (CL) and in some other parameters. For example the elite skiers nowadays use the Double Poling (DP) or V2 skating also in moderate uphill, in spite of the Diagonal Stride (DS) or V1 skating. Furthermore, the DP and V2 have a lot of resemblance and the skiers have developed their capacity of poling for larger sections, with high frequency and with greater power. Although the performances in elite skiers are extremely close to each other, and it is not easy to understand which parameters influencing the final result of a world championships competition, we are convinced that the double poling phase, which is performed hundredths times in each race, should receive the maximum attention. Furthermore, the performances are determined also by the positioning of the trunk, the shoulders, the elbows and the poles (G. Smith 1996, Holmberg 2005) in the propulsive poling phase. The aim of this study was to investigate the positioning of the upper-body limbs during the poling phase in classical techniques. Methods: The data collection was performed on 1999, WC in Ramsau, and on 2003, WC in Val di Fiemme, during various men's CCS competition. A couples of digital camcorders (SONY 50 Hz) were located, in each races, on flat section (40 meters long). Due to the technical requirement of a wide working volume, dedicated software for video analysis, with free panning, tilting and zooming TV cameras was used (Baroni et al., 1998). Calibration was performed by means DLT method. The control points for system calibration were marked out with 30-50 high rigid poles. The biomechanical model of the skier consisted of 23 landmarks, 4 of this points were used for the poles and for the skis identification. Joint angles were calculated as the absolute angles between different anatomical landmarks; the displacements of the body`s centre of mass (CG) were quantified on the average plane of track (horizontal plane) and on the orthogonal direction to this plane (vertical direction). Results: A minimum of 10 skiers were analysed in both races: the principal kinematics parameters were measured for each competitors (tab. 1) as mean values of 2 or 3 cycles; the values of the angles parameters were plotted to each others to investigate the individual patterns. Fig. 1 shows a typical stick diagram, the velocity and vertical displacement of CG (second plot), in correspondence of the flat section where skiers performed DP or DP with kick stride. In the middle and lower graph are plotted the typical patterns of the trunk, shoulder, elbow and poles angles during the 3 cycles considered. Discussion: In according with previous study (Marino 1977, Komi 1987, Bilodeau 1995, Smith 1996), we found that the faster skiers have longer cycle lengths (r=0.53 Ramsau, r=0.48 Fiemme). The kinematics patterns of shoulder, elbows and poles angles were found to be quite similar to literature data, but the values of the angle shows no correlation with the CoG velocity. However it seems that the key point of the poling is the relative positioning of the upper-body limbs to each others and the angles of the poles. For example a Elbow Angle at the PP is quite 90° in all case and not change in the first part of the poling. However the skiers adopted different strategy to perform the poling with respect to the trunk, shoulder and elbow rotations. The individual patterns of this and additional biomechanics parameters are also discussed with reference to the potential significance for the optimisation of the overall movement performance.